Palaako tuotanto Aasiasta Suomeen? Case polkupyörä - Matias Kalm; Timo Seppälä (The Research Institute of the Finnish Economy (ETLA), 2012)
– In this paper, we study the value chain of a Finnish designed bicycle and how the value added of the product is spread through the value chain in three distinct cases. In the first case the bicycle is manufactured in Finland by the researched company. In the two other cases the manufacturing of the bicycle is outsourced to the Baltic countries or to Indonesia. In addition, we analyze the geography of value added in each case. We also study how the exchange rate fluctuations affect the distribution of the value added. Our results show that the researched company creates 36% of the total value added, when the bicycle is made in its plant. The manufacturing creates 16% of the total value added. The researched company creates 27-28% of the total value added, when the production is outsourced. The value added share of Finland is 67%, when the bicycle is produced in Finland, and 58-59%, if the production is outsourced. In conclusion, the results show that outsourcing offshore is financially beneficial for the researched company and that the Finnish economy suffers from the production transfer. Furthermore, the results suggest that transferring the production away from Asia is financially and otherwise justifiable - however, the production is transferred to the Baltic countries instead of Finland. Our findings support the view that, while the low value added activities and processes are outsourced, the high value added activities are still positioned to Finland, since the outsourcing partners create only 2% of the total value added.
Keywords: F14; F23; L22; L23; L24; 330; global value chains; value added; outsourcing; exchange rates